Cluster Randomized Trial of a Church-Based Peer Counselor and Tailored Newsletter Intervention to Promote Colorectal Cancer Screening and Physical Activity Among Older African Americans. (October 2016) - Leone, Lucia A.; Allicock, Marlyn; Pignone, Michael P.; Walsh, Joan F.; Johnson, La-Shell; Armstrong-Brown, Janelle; Carr, Carol C.; Langford, Aisha; Ni, Andy; Resnicow, Ken; Campbell, Marci K.
Action Through Churches in Time to Save Lives (ACTS) of Wellness was a cluster randomized controlled trial developed to promote colorectal cancer screening and physical activity (PA) within urban African American churches. Churches were recruited from North Carolina ( n = 12) and Michigan ( n = 7) and were randomized to intervention ( n = 10) or comparison ( n = 9). Intervention participants received three mailed tailored newsletters addressing colorectal cancer screening and PA behaviors over approximately 6 months. Individuals who were not up-to-date for screening at baseline could also receive motivational calls from a peer counselor. The main outcomes were up-to-date colorectal cancer screening and Metabolic Equivalency Task (MET)-hours/week of moderate–vigorous PA. Multivariate analyses examined changes in the main outcomes controlling for church cluster, gender, marital status, weight, and baseline values. Baseline screening was high in both intervention (75.9%, n = 374) and comparison groups (73.7%, n = 338). Screening increased at follow-up: +6.4 and +4.7 percentage points for intervention and comparison, respectively ( p = .25). Baseline MET-hours/week of PA was 7.8 (95% confidence interval [6.8, 8.7]) for intervention and 8.7 (95% confidence interval [7.6, 9.8]) for the comparison group. There were no significant changes ( p = .15) in PA for intervention (−0.30 MET-hours/week) compared with the comparison (−0.05 MET-hours/week). Among intervention participants, PA increased more for those who participated in church exercise programs, and screening improved more for those who spoke with a peer counselor or recalled the newsletters. Overall, the intervention did not improve PA or screening in an urban church population. These findings support previous research indicating that structured PA opportunities are necessary to promote change in PA and churches need more support to initiate effective peer counselor programs.